The who start study suicidal behaviors across different areas of the world - De Leo, D.; Milner, A.; Fleischmann, A.; Bertolote, Y. [UNESP]; Collings, S.; Amadeo, S.; Chan, S.; Yip, P. S F; Huang, Y.; Saniel, B.; Lilo, F.; Lilo, C.; et al. (Hogrefe Publishing Group, 2013)
Background: The World Health Organization (WHO) study entitled Suicide Trends in At-Risk Territories (START) is an international multisite initiative that aims to stimulate suicide research and prevention across different areas of the globe. A central component of the study is the development of registration systems for fatal and nonfatal suicidal behaviors. Aims: This paper provides an overview of the data collected on suicidal behaviors from the participating locations in the START study. Method: Descriptive statistics on the data are presented in terms of age, sex, and method. Results: Agreater proportion of suicide deaths occurred among males. In all areas except the Philippines more females than males engaged in nonfatal suicidal behaviors. Compared to Australia, Italy, New Zealand, the Philippines, and Hong Kong SAR, in the Pacific Islands suicide most often occurs in younger age groups. Results indicate notable variations between countries in choice of method. A greater proportion of suicides occurred by hanging in Pacific Islands, while inhalation of carbon monoxide, use of firearms, ingestion of chemicals and poisons, and drug overdose were the most frequent methods of choice in other areas. Conclusion: The information drawn from this study demonstrates the enormous variation in suicidal behavior across the areas involved in the START Study. Further research is needed to assess the reliability of the established data-recording systems for suicidal behaviors. The baseline data established in START may allow the development of suicide prevention initiatives sensitive to variation in the profile of suicide across different locations. © 2013 Hogrefe Publishing.
Keywords: Culture; Start study; Suicide; Western pacific; World health organization